IS ONCOLYTIC VIROTHERAPY A VIABLE PLATFORM FOR GLIOMA TREATMENT? - Mohammad, Fahad (Journal of Postgraduate Medical Institute, 2016)
Gliomas are devastating cancers of the nervous system with poor prognosis. Their aggressiveness produces a mortality rate rarely seen with other malig-nant tumours and the lack of effective treatment has left very few options. On-colytic viruses, with their long history of experimentation, have been deemed to be a key player in the future treatment of gliomas. This review will focus on the two main contenders, adenovirus and herpes simplex virus, for glioma treatment and discuss how far the field has come since its conception. The concept of each vector and the rationales behind their use will be contrasted before discussing the future of the field. Data was located by accessing the MEDLINE database using the PubMed search system. Data was selected on the basis of the insight its information provided as well as on the dependabil -ity of the experimental method used.